Introduction: QUALIA. (March 2013) - Chumley, Lily Hope; Harkness, Nicholas
This special issue proposes that the semiotically theorized concept of 'qualia' is useful for anthropologists working on problems of the senses, materiality, embodiment, aesthetics, and affect. Qualia are experiences of sensuous qualities (such as colors, textures, sounds, and smells) and feelings (such as satiety, anxiety, proximity, and otherness). The papers in this issue, first presented in a conference in honor of Nancy Munn and her groundbreaking book, The Fame of Gawa: A Symbolic Study of Value Transformation in a Massim Society (1986), offer ethnographic accounts of the discursive, historical, and political conditions under which sensations come to be understood as being sensations of qualities – the qualia of softness, lightness, clarity, pain, stink, etc. – and in which those qualia are endowed with cultural value, whether positive or negative. The papers in this issue demonstrate that qualia are not just subjective mental experiences but rather sociocultural events of 'qualic' – and qualitative – orientation and evaluation. These papers thus provide models for the analysis of experience by calling into question what counts for social groups as the senses, materiality or immateriality, interiority, embodiment, or exteriority.